2023
DOI: 10.1109/access.2023.3314499
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Factors Influencing Higher Education Students’ Intention to Adopt Artificial Intelligence-Based Robots

Mohammed A. M. Algerafi,
Yueliang Zhou,
Hind Alfadda
et al.

Abstract: Although there has been some progress, the integration of artificial intelligence into higher education remains far from sufficient. The demand for teachers will persist for some time; however, with the introduction of AI-based robots into classrooms, the role of teachers has reduced to a minimum. The purpose of the current study was to evaluate Chinese higher education students' intentions to adopt AI-based robots for educational purposes. Based on the TAM3 model, the current study proposes 14 hypotheses to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…Instead, a more balanced approach may involve strategically integrating AI assistants as supplementary tools to enhance certain aspects of the writing process while maintaining a strong emphasis on human instruction and guidance (An et al, 2023;Lin et al, 2022;Wongras & Tanantong, 2023;Wu et al, 2022). Ultimately, the role of AI in academic writing instruction may continue to evolve, but human instructors and their expertise in teaching the complexities of academic discourse are likely to remain essential components of university-level writing education (Algerafi et al, 2023;Cheong et al, 2023;Teng et al, 2022;Wilby, 2022). Subsequent sections further discuss the findings in light of the research questions and theoretical framework.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Instead, a more balanced approach may involve strategically integrating AI assistants as supplementary tools to enhance certain aspects of the writing process while maintaining a strong emphasis on human instruction and guidance (An et al, 2023;Lin et al, 2022;Wongras & Tanantong, 2023;Wu et al, 2022). Ultimately, the role of AI in academic writing instruction may continue to evolve, but human instructors and their expertise in teaching the complexities of academic discourse are likely to remain essential components of university-level writing education (Algerafi et al, 2023;Cheong et al, 2023;Teng et al, 2022;Wilby, 2022). Subsequent sections further discuss the findings in light of the research questions and theoretical framework.…”
Section: Discussionmentioning
confidence: 99%
“…Ensuring a thorough and practical approach to academic writing education involves striking a balance between the advantages of AI and the fundamental abilities developed in traditional writing courses (Ali et al, 2020;Sajjad et al, 2023;Makarius et al, 2020). However, researchers observed that overreliance might result in a deterioration of students' cognitive abilities related to analytical reasoning and a diminishment of the individual's originality in written expression (Algerafi et al, 2023;Berssanette & de Francisco, 2022;Lin et al, 2022;Salvagno et al, 2023). For example, AI tools may have limited understanding of subject matter expertise, which can result in potential mistakes or a lack of thorough analysis (Dong, 2023;Nazari et al, 2021;.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations